2004
DOI: 10.1159/000080874
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Molecular Biology-Based Assays for the Detection of GB Virus C/Hepatitis G Virus in Clinical Specimens

Abstract: Objective: The present study was performed to evaluate the reliability of three reverse transcription-polymerase chain reaction (RT-PCR) assays, one commercial and two ‘homebrew’, for GB virus C (GBV-C)/hepatitis G virus (HGV) RNA detection in clinical specimens. We, therefore, investigated the virus prevalence with the method that gave us the best performances. Methods: The commercial assay amplified sequences from the viral 5′-untranslated region (5′UTR) and non-structural 3 (NS3) region. The non-commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
1
0
2
Order By: Relevance
“…Primer selection is a key point in the development of successful PCR strategies. Authors comparing genomic regions and different primers among the same target gene in the GBV-C genome concluded that the 5'UTR is the most stable and conserved region and in addition provided a valuable suggestion of "best primers" 1,3,18 . The TaqMan assay here described achieved the same sensitivity as a nested-PCR proposed by ANDONOV et al 1 , in a more convenient and automated format.…”
Section: Discussionmentioning
confidence: 99%
“…Primer selection is a key point in the development of successful PCR strategies. Authors comparing genomic regions and different primers among the same target gene in the GBV-C genome concluded that the 5'UTR is the most stable and conserved region and in addition provided a valuable suggestion of "best primers" 1,3,18 . The TaqMan assay here described achieved the same sensitivity as a nested-PCR proposed by ANDONOV et al 1 , in a more convenient and automated format.…”
Section: Discussionmentioning
confidence: 99%
“…Tali dosaggi erano previsti al momento dell'arruolamento (T=0), al momento della raccolta dei linfociti del sangue periferico (T=1), prima delle alte dosi di chemioterapia (T=2), circa 10-15 giorni dopo la reinfusione dei linfociti periferici (T=3) e a 2 mesi dalla reinfusione (T=4). Estrazione del DNA da campioni di siero Allo scopo di ottimizzare la quantificazione assoluta della carica virale di EBV nel siero di campioni clinici mediante Real Time PCR, sono state valutate le efficienze di due metodi di estrazione, uno commerciale (QIAamp DNA Mini kit, QIA-GEN) e uno tradizionale in cui venivano impiegati solventi organici, previa precipitazione delle particelle virali con soluzione di polietilenglicole (PEG) (2). Il secondo metodo di estrazione prevede un primo passaggio in cui vengono precipitati per 1 ora in ghiaccio 200 µl di siero in 200 µl di soluzione al 20% di PEG.…”
Section: Materiali E Metodi Curva Standard Sensibilità E Riproducibiunclassified
“…En contraste, los individuos que desarrollan una infección persistente, presentan detección del ARN viral en suero por largos periodos de tiempo y ausencia de anticuerpos anti-E2. 7 El ARN viral constituye un marcador de infección que puede ser analizado mediante RPC-TR, usando partidores dirigidos a las regiones conservadas 5´NTR, NS3 y NS5 8 . Por su parte, la detección de los anticuerpos contra la glicoproteína E2 (anti-E2) mediante ELISA, revelan la existencia de infección pasada y sólo en un pequeño porcentaje (< 5%) se ha detectado la presencia simultánea de anticuerpos y de ARN viral 9 .…”
unclassified